Model Belief Adjustment dalam Pengambilan Keputusan Investasi Berdasarkan Informasi Nonakuntansi - Anita Anggraeni; Luciana Spica Almilia (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2017)
The purpose of this study is to examine is there any difference on investment decision making among participant that received good news information followed by bad news compared with participant that received bad news information followed by good news on the SbS and EoS information disclosure pattern, also long and short information series. The experiment design in this study is 2x2x2 mix design subject, which is the information disclosure pattern (step by Step and End of Sequence), information order (good news followed by bad news), and information series (long and short infomation series). The Independent Sample t-test used to examined the research hypothesis. The amount of participant involved on this study are 96 college students in STIE Perbanas Surabaya in Accountant and Management major. The result show that there were difference on investment decision making among participant that received good news information followed by bad news compared with participant that received bad news information followed by good news on the SbS information disclosure pattern and long information series and also occurs recency effect.Abstrak Tujuan penelitian ini adalah menguji perbedaan keputusan investasi antara partisipan yang menerima informasi good news diikuti bad news dibandingkan dengan partisipan yang menerima informasi bad news diikuti good news, baik pada pola penyajian SbS maupun EoS dan seri informasi panjang dan pendek. Penelitian ini menggunakan metoda eksperimen 2x2x2 mix design, yaitu pola penyajian (step by step dan end of sequence) dan urutan informasi (good news diikuti bad news dan bad news diikuti good news) dan seri informasi (informasi panjang dan informasi pendek). Independent Sample t test digunakan untuk menguji hipotesis penelitian. Jumlah partisipan dalam penelitian ini adalah 96 mahasiswa Akuntansi dan Manajemen STIE Perbanas Surabaya. Hasil penelitian menunjukkan bahwa terdapat perbedaan dalam pengambilan keputusan investasi dan terjadi recency effect bagi partisipan yang menerima good news diikuti bad news dibandingkan dengan partisipan yang menerima informasi bad news diikuti bad news pada pola penyajian SbS dan seri informasi panjang.